Stochastic regularization of ill-posed problems of heat transfer - Panin, V.V.; Krivoshey, F.A.; Bogdan, Yu.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The stochastic approximation of the parabolic equation of heat conduction and its subsequent averaging over realizations of random parameters leads to an equation of the hyperbolic type for the average values of transfer functions. On a basis of this equation, the statements of inverse problems concerning the restoration of boundary conditions are well-posed.